2021
DOI: 10.1002/ejoc.202100447
|View full text |Cite
|
Sign up to set email alerts
|

[Ag]2[B12Cl12] as a Catalyst in PhICl2 Mediated Chlorination**

Abstract: The weakly coordinating dianion [B 12 Cl 12 ] 2À originates from a family of carboranes typically reserved for application in coordination chemistry. Herein, we show that its readily accessible Ag(I) salt, [Ag] 2 [B 12 Cl 12 ], can be used as a catalyst in the PhICl 2 mediated chlorination of arenes, alkenes, and alkynes. The promising activity displayed by [Ag] 2 [B 12 Cl 12 ] over a variety of commercially available Ag(I) sources merits its incorporation to the toolkit of commonly screened silver catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…PhI and H 2 O 2 /HCl). 5,6 On standing in solution or at room temperature, PhICl 2 degrades into PhI and Cl 2 , which in solution occurs over a matter of hours. 7 PhIF 2 and related derivatives (most often with tolyl as the aryl group) are commonly used as a fluorinating agents.…”
mentioning
confidence: 99%
“…PhI and H 2 O 2 /HCl). 5,6 On standing in solution or at room temperature, PhICl 2 degrades into PhI and Cl 2 , which in solution occurs over a matter of hours. 7 PhIF 2 and related derivatives (most often with tolyl as the aryl group) are commonly used as a fluorinating agents.…”
mentioning
confidence: 99%
“…56 Reaction of PhICl 2 with [Ag] 2 [B 12 Cl 12 ] in an attempt to generate [PhI] 2+ resulted instead in the generation of chlorinated iodobenzene (Scheme 14). 57 It was subsequently found that this transformation also occurs using catalytic amounts of [Ag] 2 [B 12 Cl 12 ]. Iodobenzene is not chlorinated by Cl 2 in the absence of a strong Lewis acid catalyst, therefore it was rationalized that a more activated electrophilic chlorine source was in play and proposed to be transient [PhICl] + .…”
Section: Activation Of Phiclmentioning
confidence: 99%
“…A variety of arenes and other unsaturated molecules that do not react with PhICl 2 could be chlorinated using catalytic loadings of [Ag] 2 [B 12 Cl 12 ]. 57 A major limitation is that nothing less activated than PhI can be used as a substrate, as in these cases chlorination of PhI is the dominant product. When pyridine was used as a substrate a complex mixture was obtained.…”
Section: Activation Of Phiclmentioning
confidence: 99%